Oscillate boiling from electrical microheaters - Nguyen, Dang Minh (2019)
Oscillate boiling offers excellent heat transfer at temperatures above the Leidenfrost temperature. Here we realize an electrical microheater with an integrated thermal probe and resolve the thermal cycle during the high-frequency bubble oscillations. A thermal rate of 10^8 K/s is found, indicating its applicability for compact and rapid heat transfer from microelectrical devices. We also report another oscillate-boiling regime occurring at lower heating power where the oscillation becomes unstable and halts after several milliseconds.